Self-reported risky sexual practices among adolescents and young adults in Botswana - Unoda Chakalisa; Kathleen Wirth; Kara Bennett; Etienne Kadima; Kutlo Manyake; Tendani Gaolathe; Pam Bachanas; Tafireyi Marukutira; Refeletswe Lebelonyane; Scott Dryden-Peterson; Lisa Butler; Mompati Mmalane; et al. (AOSIS, 2019)
Background: Adolescents and young adults account for more than one-third of incident Human Immunodeficiency Virus (HIV) infections globally. Understanding sexual practices of this high-risk group is critical in designing HIV targeted prevention programming. Objectives: To describe self-reported risky sexual practices of adolescents and young adults aged 16-24 years from 30 Botswana communities. Methods: Cross-sectional, self-reported age at sexual debut; number of sexual partners; condom and alcohol use during sex; intergenerational sex; and transactional sex data were collected. Modified Poisson estimating equations were used to obtain univariate and multivariate-adjusted prevalence ratios (PR) and 95% confidence intervals (CI) comparing engagement in different sexual practices according to gender, accounting for the clustered design of the study. Results: Among the 3380 participants, 2311 reported being sexually active with more females reporting being sexually active compared to males (65% vs. 35%, respectively; p < 0.0001). In univariate analyses, female participants were more likely to report inconsistent condom use (PR 1.61; 95% CI 1.44-1.80), intergenerational sex (PR 9.00; 95% CI 5.84-13.88) and transactional sex (PR 3.46; 95% CI 2.07-5.77) than males, yet less likely to report engaging in sex before age 15 years (PR 0.59; 95% CI: 0.41-0.85), using alcohol around the time of intercourse (PR: 0.59; 95% CI 0.45-0.76) or having ≥ two partners in the last 12 months (PR 0.65; 95% CI 0.57-0.74). Conclusions: Self-reported risky sexual practices of adolescents and young adults in Botswana differed significantly between males and females. Gender-specific risky sexual practices highlight the importance of developing tailored HIV prevention programming.